2011
DOI: 10.3329/jsr.v3i3.7129
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intensive and Semi-intensive Feeding System on Productive and Reproductive Performances of Native Sheep

Abstract: The experiment was conducted with forty four pre-pubertal stages female lambs of 12.5±2.5 kg average live weight and 7.5±0.5 months of average age. Animals were equally and randomly allocated into two feeding groups, intensive and semi-intensive feeding systems with 22 animals in each group. Under intensive system, animals were fed concentrate mixture (15.0% crude protein (CP); 11 MJ metabolizable energy (ME)/kg dry matter (DM)) at the rate of 1.5% of live weight with ad libitum green grass from May to Novembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 5 publications
2
10
3
Order By: Relevance
“…In adverse climatic condition farmers have to house their sheep providing stall feeding with tree leaves, natural grasses and kitchen wastes. Sheep reared in the villages of Bangladesh solely depend upon the grasses, which contain higher percentage of crude fiber (Ghosh et al,1983).Feed and fodder scarcity is a major limiting factor in Bangladesh resulting in low productivity, poor growth and reproduction of sheep (Sultana et al, 2011). There is high demand of land for crop production, urbanization and industrialization in our country.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In adverse climatic condition farmers have to house their sheep providing stall feeding with tree leaves, natural grasses and kitchen wastes. Sheep reared in the villages of Bangladesh solely depend upon the grasses, which contain higher percentage of crude fiber (Ghosh et al,1983).Feed and fodder scarcity is a major limiting factor in Bangladesh resulting in low productivity, poor growth and reproduction of sheep (Sultana et al, 2011). There is high demand of land for crop production, urbanization and industrialization in our country.…”
Section: Introductionmentioning
confidence: 99%
“…They are mostly reared by family members under zero input in char or coastal areas and also in plane land (Sultana et al, 2011). Most of the sheep (84.80% of the total) is reared under low input system and the rest 15.20% is found under medium input system (BBS, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Since, the species has the ability to acclimatize with harsh coastal region climate, profitability with poor husbandry management and feeding supplementation, rural farmers of Bangladesh always prefer to kept sheep for their livelihood (Sultana et al, 2011). In addition, sheep are kept as a family tradition of livestock rearing particularly in coastal areas of Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
“…Kumar [12], Sultana et al [13] and Abdelqader et al [14] studied the potential impacts of adapting sheep and goats in semi-intensive and intensive systems in similar arid regions to the UAE arid land. Kumar [12] concludes that goat rearing in India is rewarding in both semi-intensive and intensive systems.…”
Section: Introductionmentioning
confidence: 99%
“…Kumar [12] concludes that goat rearing in India is rewarding in both semi-intensive and intensive systems. Sultana et al [13] found that semi-intensive feeding systems were found to be more efficient, testing native sheep species in Bangladesh. However, the authors found that the intensive system is more efficient using lamb survivability criteria.…”
Section: Introductionmentioning
confidence: 99%